Preparation and physicochemical characterization of meloxicam orally fast disintegration tablet using its solid dispersion - Zahra Shoormeij; Azade Taheri; Alireza Homayouni (Universidade de São Paulo, 2018)
ABSTRACT Meloxicam (MLX) is a non-steroidal, anti-inflammatory drug that is prescribed in the treatment of rheumatoid arthritis and osteoarthritis. MLX is practically insoluble in water and exhibits a slow onset of action. In this study, MLX solid dispersions (MLX SDs) were prepared to improve the water solubility of this poorly water-soluble drug. Then orally disintegrating tablets (ODT) of MLX were developed using MLX SD to decrease the onset of action of this drug. MLX, poloxamer 188, and crospovidone of different ratios were melted in molten poloxamer 188 as a hydrophilic carrier. The optimum SD with the highest saturation solubility in water (13.09±0.34 microgram/mL) consisting of MLX: poloxamer 188: crospovidone in the ratio of 1:2:0 was used for the preparation of MLX ODTs. MLX ODTs were prepared by the direct compression method and optimized by the 23 factorial design. The effect of the superdisintegrant concentration, the mannitol-avicel ratio, and the level of compression force on the disintegration time, hardness, and percent of dissolved MLX from MLX ODTs after 30 min was evaluated. DSC and XRD analysis approved an amorphous form of MLX in SDs. The optimized ODT formulation containing 10% of superdisintegrant, and mannitol and avicel in the ratio of 4:1 respectively was compressed using a high level of compression force. The optimized ODT showed hardness (34.37±2.1 N) and friability (1.26±0.04%). This formulation showed a rapid disintegration in 12.66±2.5 seconds, which 82.66±5.1% of the MLX released within 30 min. MLX ODTs, prepared from MLX SD, could be introduced as a suitable dosage form of MLX with improved solubility and the onset of action.